The Mediatization of Sacred Texts: Theological Shifts and Myth-Making in the Islamic Pop Song “Hafidz Qur’an” - Mohammad Salahuddin Al-Ayyuubi; Nur Laily Fauziyah (Jawahir Al-Ahadis, 2026)
The phenomenon of the mediatization of Islam has spurred the adaptation of sacred texts (hadith) into the realm of popular music, which has sparked tension between the effectiveness of da’wah and the constraints of classical fiqh. This study examines the transformation of the hadith “crown of light” into an Islamic pop song titled “Hafidz Qur’an” using a four-dimensional analytical framework: Genette’s hypertextuality, Hutcheon’s theory of adaptation, Barthes’s semiotics, and Hall/Jauss’s reception studies. The results reveal an eschatological simplification; theological rewards are transformed into an emotional appeal (a child’s love for their parents), and the requirements of reading and practicing the Qur’an are narrowed down to merely the status of a Hafiz. This aligns with the tradition of using Da’if Hadith (those deemed weak) specifically for the purposes of Fada’il al-A’mal (the virtues of righteous deeds, not the establishment of Sharia law). The semiotics of the song and various children’s vocal covers were found to construct a cultural myth of the “righteous child,” which successfully defused the controversy surrounding music. Through YouTube comment data, the reception study confirms the strength of dominant coding, meaning the audience receives the message exactly as intended by its creator. These emotional lyrics even supplant the original sacred text in the listeners’ minds. In short, this song serves as a highly effective model of modern da’wah. As a practical implication, these findings can guide the formulation of digital da’wah content policies to design works that resonate emotionally without straying from the essence of religion